Anzaldúa and 'the new mestiza': A Chicana dives into collective identity - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s María Henríquez-Betancor Universidad de Las Palmas de Gran Canaria, Spain   ABSTRACT In this article I analyze how Gloria Anzaldúa's seventh essay in Borderlands/La Frontera:The New Mestiza, titled "La conciencia de la mestiza: Towards a New Consciousness", condenses and portrays a development towards the mestiza consciousness presented in the first six essays in the book. This is a well-structured as well as fluid process in which each step guides us in a complex identity-building awareness. This process is an inner journey as well as an evolution in the public scene where the "new mestiza" has to revise and reinvent herself in several ways in order to acquire "the mestiza consciousness". This essay is also a clear example in which Anzaldúa represents three voices: the "I", the "we" and the "she". These voices are one of Anzaldúa's strategies for diving into what she understands as her collective identity as a Chicana and as a "new mestiza". As will be shown in this article, the author moves among these voices for various purposes of identity-construction.